2019
DOI: 10.1111/imig.12606
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of UN Peacekeeping Operations on Human Trafficking

Abstract: While United Nations (UN) peacekeeping operations (PKOs) are generally considered to reduce the likelihood of civil war recurrence, attention in recent years has shifted to understanding the dynamics unique to post‐Cold War peacekeeping, including the changing makeup and mandate of PKOs, and associated patterns of peacekeeper misconduct. While several studies of misconduct emphasize peacekeepers’ implication in sexual exploitation and abuse of host country citizens, this study goes the next step by assessing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Ten articles centred on two closely related unintended consequences produced by peacekeeping missions. The first concerns patterns of peacekeeper misconduct, more specifically the sexual exploitation and abuse (SEA) of host country citizens (Aning & Edu‐Afful, 2013; Fluri, 2012; Jennings, 2010; Kolbe, 2015), while the second concerns observed increases in human sex trafficking (Horne & Barney, 2019; Jennings, 2010; Smith & Smith, 2011). Both can be categorised as process‐based, negative spillover effects, although in some UN missions, there are blurred lines between gender‐focused work and peacekeeping goals (which would thus indicate a backfire effect).…”
Section: Five Key Unintended Gender Effects Of Aidmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten articles centred on two closely related unintended consequences produced by peacekeeping missions. The first concerns patterns of peacekeeper misconduct, more specifically the sexual exploitation and abuse (SEA) of host country citizens (Aning & Edu‐Afful, 2013; Fluri, 2012; Jennings, 2010; Kolbe, 2015), while the second concerns observed increases in human sex trafficking (Horne & Barney, 2019; Jennings, 2010; Smith & Smith, 2011). Both can be categorised as process‐based, negative spillover effects, although in some UN missions, there are blurred lines between gender‐focused work and peacekeeping goals (which would thus indicate a backfire effect).…”
Section: Five Key Unintended Gender Effects Of Aidmentioning
confidence: 99%
“…Third, the UN presence suppresses local criminal networks, opening the market for international trafficking entrepreneurs. Fourth, post‐conflict circumstances make it easier for human trafficking to take place in the absence of a properly functioning police force and in the presence of a weak judiciary and penal system (Horne & Barney, 2019). Meta‐analyses of several peacekeeping missions (taking into account both qualitative and quantitative data) found that increases in trafficking follow discernible patterns (Horne & Barney, 2019; Smith & Smith, 2011).…”
Section: Five Key Unintended Gender Effects Of Aidmentioning
confidence: 99%
See 1 more Smart Citation
“…The migratory effects of peacekeeping missions are well documented [54][55][56]. When internally displaced people flock to the area around a blue-helmet compound, the effects can be short-term.…”
Section: Migration Effectsmentioning
confidence: 99%